1988
DOI: 10.1093/geronj/43.1.m9
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infections In Long-Term Facilities

Abstract: We studied the incidence and prevalence of hospital-acquired infections in our intermediate-care units and the Nursing Home Care Unit at the Veterans Administration Medical Center, Johnson City, TN over a 4-year period (1980 through 1983). The global infection rate was 3.86 per 1,000 patient care days. The lower respiratory tract was the most common site of infection, followed by urinary tract infections, skin infections, bacteremia, wound infections, and infections at other sites. The prevalence study conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 0 publications
3
77
0
Order By: Relevance
“…It is very common, but our work showed it to cause death in only 8%, mostly when the inflammation involved the kidneys, as in purulent pyelonephritis. These two types of infections, bronchopneumonia and UTI, are often nosocomial in origin (19). Furthermore, chronic UTI may predispose the lungs for development of a fatal bronchopneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…It is very common, but our work showed it to cause death in only 8%, mostly when the inflammation involved the kidneys, as in purulent pyelonephritis. These two types of infections, bronchopneumonia and UTI, are often nosocomial in origin (19). Furthermore, chronic UTI may predispose the lungs for development of a fatal bronchopneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rate ranges from 20% to 50%, with a rate as high as 80% reported in some studies [4][5][6][7][8]. From these reports, factors that are commonly cited as being associated with pneumonia are advanced age, residing in an environment such as an institutional setting where risk of infection is higher, predisposing medical conditions, reduced mental status, reduced functional status, tube feeding, gastroesophageal reflux, poor nutritional status, oropharyngeal colonization of pathogenic bacteria, reduced pulmonary clearance, and immunocompromise [5,[9][10][11][12][13][14][15][16][17][18][19][20].Many recent studies have shown a relationship between pneumonia and oropharyngeal dysphagia with aspiration of food or liquid [21][22][23][24][25][26][27][28][29][30]. Since dysphagia predisposes to aspiration, the relationship between dysphagia and aspiration pneumonia might appear obvious, but evidence for this has not always been found [31][32][33].…”
mentioning
confidence: 99%
“…The overall mortality rate ranges from 20% to 50%, with a rate as high as 80% reported in some studies [4][5][6][7][8]. From these reports, factors that are commonly cited as being associated with pneumonia are advanced age, residing in an environment such as an institutional setting where risk of infection is higher, predisposing medical conditions, reduced mental status, reduced functional status, tube feeding, gastroesophageal reflux, poor nutritional status, oropharyngeal colonization of pathogenic bacteria, reduced pulmonary clearance, and immunocompromise [5,[9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…These infections are largely endemic and have an overall infection rate that ranges from 1,8 to 13,5 infections per 1000 resident care days (Strausbaugh LJ & Al, 2000). The variability of prevalence (Cohen E & Al, 1979;Garibaldi R & Al, 1981;Standfast SJ & Al, 1984;Setia U & Al, 1985;Scheckler W & Peterson P, 1986;Alvarez S & Al, 1988;Magaziner J & Al, 1991;Steinmiller A & Al, 1991;Eikelenboom-Boskamp A & Al, 2011) and incidence (Magnussen M & Robb S, 1980;Farber BF & Al, 1984;Nicolle LE & Al, 1984;Franson T & Al, 1986;Scheckler W & Peterson P, 1986;Viahov D & Al, 1987;Alvarez S & Al, 1988;Schicker JM & Al, 1988;Hoffman N & Al, 1990;Jacobson C & Strausbaugh LJ, 1990;Darnowsky S & Al, 1991;Jackson M & Al, 1992) rate of infections, reflects differences in patients populations in different study institutions, as well as differing surveillance definitions and methods for case ascertainment .…”
Section: Occurrence Of Endemic Infectionsmentioning
confidence: 99%